Recent Advances on the Total Syntheses of the Communesin Alkaloids and Perophoramidine - Trost, Barry M. (Chemistry, 2015)
The communesin alkaloids are a diverse family of Penicillium-derived alkaloids. Their caged-polycyclic structure and intriguing biological profiles have made these natural products attractive targets for total synthesis. Similarly, the ascidian-derived alkaloid, perophoramidine, is structurally related to the communesins and has also become a popular target for total synthesis. This review serves to summarize the many elegant approaches that have been developed to access the communesin alkaloids and perophoramidine. Likewise, strategies to access the communesin ring system are reviewed.